HAK DAN KEWAJIBAN ANAK TERTUA DALAM GARIS PATRILINEAL TERKAIT DENGAN PEMBAGIAN HARTA WARISAN SECARA HUKUM ADAT - Arjonius Halawa (LPPM Universitas Nias Raya, 2025)
Giving something to heirs or affected families when someone dies is called inheritance. Three inheritance laws—customary inheritance law, Islamic inheritance law, and civil inheritance law—apply in the division of inheritance in Indonesia. The research problem is that in Olayama Village the distribution of inheritance to the eldest child is done differently compared to the second, third and so on. This research, which was conducted in Olayama Village, Huruna District, South Nias Regency, aims to determine the rights and responsibilities of the eldest child in the patrilineal line in the distribution of inheritance regulated by customary law.